Cardiac Tamponade: An Alternative Procedure for Late Feticide - Chia-Hsiang Chen; Hsin-Chin Hsieh; Horng-Der Tsai; Tze-Ho Chen; Ming Chen (Elsevier, 2009)
Objective: Improvements in equipment and diagnostic skills mean that more abnormalities can now be detected antenatally, thus increasing the demand for pregnancy termination at later stages of gestation. Potassium chloride injected into the fetal circulation is the most frequently used procedure. In this study, we propose a new method of feticide using injection of normal saline into the fetal pericardial space to induce cardiac tamponade, resulting in late fetal reduction with minimal maternal risk. Case Report: A 32-year-old, gravida 6, woman was a carrier of a balanced translocation 45, XX, der(2), t(2,22), and had a poor obstetric history. Chorionic villus sampling was performed, and the results revealed the fetus to be a balanced translocation carrier, like the mother. Microcephaly was detected during the third trimester and amniocentesis was performed. The results showed a 45, XX, der(2)t(2;22)(q37, q11.2)mat, −22 karyotype. After counseling, the mother elected to undergo pregnancy termination. Feticide was performed before labor induction. However, she experienced discomfort when a minimal amount of potassium chloride (3 mEq) was injected into the fetal heart, without inducing fetal asystole. We, therefore, induced cardiac tamponade using 10 mL of normal saline instilled into the fetal pericardial space. Fetal asystole was noted. The whole procedure was performed without incident, and termination was achieved by hysterotomy after informed consent was given. Conclusion: Many methods of feticide have been used, including injection of potassium chloride, lidocaine, digoxin or hyperosmolar urea into the fetal circulation. However, these methods all use medications or compounds with some potential for maternal toxicity or side effects. We provide a relatively safe and effective method of feticide for use in late termination of pregnancy.